The translation strategy of strange tales from a Chinese studio: an analysis of domestication and foreignization in the East and the West - Wei, Mian; Zainal, Zainor Izat; Wong, Lingyann (Hacettepe University, 2024)
Strange Tales from a Chinese Studio, a renowned classical literary work by Pu Songling from the Qing Dynasty, has been translated into English by Herbert Giles (1842) and John Minford (2006), both retaining the same title. This study examines and compares these two English translations, analysing their respective translation strategies, which can be broadly categorized into domestication and foreignization. The analysis is framed within Lawrence Venuti’s theoretical framework, providing the basis for examining the strategies employed in each version. The study focuses on two primary aspects: the strategies and methods used in translating cultural terms, and the characteristics of the translations concerning type-token ratios, word length, and sentence length. The comparative analysis reveals that Giles predominantly employs a domestication approach, while Minford favours a foreignization strategy. However, these findings represent tendencies rather than rigid principles, highlighting the necessity for adaptable approaches to achieve effective translation outcomes.